Análisis de la eficiencia de la turbina Michell Banki y su aplicación en las pico centrales hidroeléctricas. - Curimilma Rivera, Edison Fernando (2011)
The present investigation has as objective the use of the hydraulic energy by means of the use of the turbine Michell Banki in the generation of the electricity, using like fundamental base the energy of the water and this way giving energy solutions in several places where it can take advantage this non renewable resource efficiently as it is rural several areas of our county of Loja. The investigation is structured in introduction, six chapters, conclusions and recommendations. A compilation was carried out of each one of the necessary contents for the development of this investigation, establishing an appropriate design based on mathematical calculations. Once designed the system, a lever the one was coupled which allows to brake the turn of the rotor and with this to find the highest point in efficiency of hydraulic this system, he/she also shows up a methodology for the construction of the turbine mediating drawings in the software AUTOCAD 2009